الدور الأخلاقي والقيمي الذي يقوم به بعض نماذج الشعر العربي في الحفاظ على البيئة والتنمية المستدامة - خيار, محمد مختار أحمد; محمد, محمد أحمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study is presented in response to the call of the Fourth International Conference entitled “Contemporary Scientific Research and Its Role in Achieving the Sustainable Development Goals,” convened on August 26–27, 2025, under the auspices of the Faculty of Educational Sciences and Teacher Training, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia. The paper, entitled “The Ethical and Value-Based Role of Selected Models of Arabic Poetry in Preserving the Environment and Achieving Sustainable Development,” seeks to demonstrate that Arabic poetry conveys moral principles capable of effectively guiding sustainable development efforts. By promoting public awareness of these values, poets contribute to shaping the attitudes and behaviors necessary for successful environmental and social transformation. The research is structured into two main axes: the first addressing environmental values, and the second focusing on ethical values. The findings provided comprehensive answers to the research questions, showing that Arabic poetry is replete with texts rich in ethical and environmental concerns. Such poetry has played a vital role in instilling noble values in humans toward their environment. Although many of these works arose from modest personal experiences, they were composed in eloquent language and stylistic forms which, as the textual analysis indicates, reflect a strong commitment to reinforcing fundamental ethical principles for the protection of the environment and the advancement of sustainable development in their societies. These poetic contributions thus constitute a valuable cultural heritage that merits recognition within sustainable development policies. The researchers employed the descriptive-analytical method, using inference as one of its key tools.